APPLICATION OF MATHEMATICAL APPROACHES IN MEDICINE ON THE EXAMPLE OF FOLLICULAR THYROCYTES SECRETORY ACTIVITY STUDY - Ryabukha, O.I. (World of Medicine and Biology, 2019)
Application of the information technologies to the process of data analysis, obtained during medical research, helps find out and explain the activity patterns of certain organs or their systems, their interrelations and interaction, as well as study the main and transitional functioning stages of any biological subject. The very mathematical study itself, being the higher level of cognition, permits to clearly observe the dependency of certain phenomena on other ones, and this gives us the opportunity to formulate hypotheses concerning interdependence of various systems functioning in an integral living organism. The study results of the mathematical approaches application to the study of secretory function of the thyrocyte, the basic morphofunctional thyroid unit have been presented. Development and analysis of the profile correlation pictures concerning the follicular thyrocytes secretory potential and further data integration helped determine the patterns and the peculiarities of the thyrocyte secretory function in various states: normal, increased and decreased functional activity.
Keywords: follicular thyrocyte; cytophysiologies; сorrelation analysis; сorrelation portrait; expert systems